Conservação in situ e produção de frutos da mangabeira (Hancornia speciosa GOMES) no Estado de Sergipe - Vieira, Thiago Roberto Soares (2023)
The extraction of Non-Timber Forest Products can guarantee income for several families through the sustainable use of natural resources. In the state of Sergipe, there are examples of extractivism such as mangaba (Hancornia speciosa Gomes) on the coast of the state of Sergipe. In the restinga area is the territory of the mangaba collectors, recognized for the social, economic and environmental aspects that are related to the extractive practice of this differentiated group. In this context, there is the Agroextractive Settlement Project (PAE) São Sebastião, Pirambu-SE. In this way, the research was developed in two central axes that seek to dialogue in an interdisciplinary way, in which academic methods, associated with non-scientific practices, served to elucidate the complexity of the societynature relationship of the present study. The two axes of the research were: Axis 1 (potential distribution) and Axis 2 (fruit production). In Chapter 1 entitled: Biodiversity hotspots for conservation of Hancornia speciosa Gomes aimed to predict the potential occurrence of the species in areas of high use of its fruits. The maximum entropy method was used to detect distribution patterns of H. speciosa in variable environments. The diversity of four natural populations located in extractive areas was determined by ISSR molecular markers. The prediction of occurrence indicates a reduction in the areas of occurrence, mainly due to anthropic actions. The populations of Baixa Grande, São Sebastião, Pontal and Riboleirinha are hotspots for H. speciosa in Sergipe. It is suggested the implementation of public policies aimed at the conservation of priority populations. In Chapter 2 entitled: Production of fruits of mangabeira (Hancornia speciosa Gomes) in the PAE São Sebastião-Pirambu-SE, the objective was to evaluate the production of fruits, relating to the chemical attributes of the soil, the dendrometric characteristics and the environmental condition, of mangabeiras naturally occurring and planted in the Agroextractive Settlement Project (PAE) São Sebastião, Pirambu, Sergipe, Brazil. The study was carried out with two groups of individuals of H. speciosa, those of pre-existing natural occurrence in the area and those planted by the settlers. 12 matrices were selected, also indicated by the two residents of the settlement, 06 of which were naturally occurring and 06 were planted, in which fruit production was monitored – all the fruits of these mangabeiras were collected and weighed. The dendrometric data of the matrices were measured: crown diameter (Dcup), diameter at 30 cm from the ground (D30) and height. There was no significant difference in fruit production between native and planted individuals. Among the variables analyzed, the nutrients Phosphorus and Potassium and the dendrometric variables Dtop and Height had a positive correlation with fruit production. The results brought in this study confirm the importance of strengthening and applying conservation strategies for the mangabeira through the creation of specific laws that prevent its felling and areas that protect the species through sustainable use.